The soft side of knowledge management in health institutions - Johannessen, Jon-Arild (Emerald points., 2021)
Why are hospitals so difficult to manage? It is agreed that cost-effectiveness is important, but knowledge-effectiveness is as equally essential as knowledge, skills and attitudes are the most critical competence factors in hospitals. Managing, controlling, and communicating knowledge within social systems, from the management perspective, as well as integrating information processes, vision, goals and altering the course which the system is leading can help ease the task of hospital management. The innovative contribution of The Soft Side of Knowledge Management in Health Institutions lies in its exploration of how a knowledge perspective and knowledge-effectiveness can contribute to improving hospital leadership and organisation from a continuous-change perspective. Focused on knowledge management, information, communication, organizational learning, tacit knowledge, and negotiations within hospitals, the lessons and insights in this volume will appeal to both researchers and hospital managers alike.